A new mitochondrial gene order in the banded cusk-eel Raneya brasiliensis (Actinopterygii, Ophidiiformes). Issue 1 (2nd January 2019) - Fromm, Amir; Atkinson, Stephen D.; Alama-Bermejo, Gema; Cartwright, Paulyn; Bartholomew, Jerri L.; Huchon, Dorothée
Abstract: The complete mitochondrial genome of the banded cusk-eel, Raneya brasilensis (Kaup, 1856), was obtained using next-generation sequencing approaches. The genome sequence was 16, 881 bp and exhibited a novel gene order for a vertebrate. Specifically, the WANCY and the nd6 – D-loop regions were re-ordered, supporting the hypothesis that these two regions are hotspots for gene rearrangements in Actinopterygii. Phylogenetic reconstructions confirmed that R. brasiliensis is nested within Ophidiiformes. Mitochondrial genomes are required from additional ophidiins to determine whether the gene rearrangements that we observed are specific to the genus Raneya or to the subfamily Ophidiinae.